Characteristics of Guava Probiotic Drink on Various Fruit Type and Fermentation Time - Fi’isyatin Ayu Rochmiyah; Dedin Finatsiyatull Rosida; Andre Yusuf (Food Science and Technology Journal (Foodscitech), 2022)
Guava (Psidium guajava) is a fruit that may be used as raw material for probiotic drinks. Guava contains fructose, and glucose which are used by lactic acid bacteria during the fermentation process. Use guava as the basic ingredient of probiotic drinks can increase the selling value of guava. The production of guava probiotics involves the bacterium Lactobacillus casei FNCC 0090 as a probiotic agent. This study aimed to determine the effect of fermentation time and type of Psidium guajava fruit on the characteristics of probiotic drink from guava. This study used a Randomized Complete Block Design (RCBD) with a factorial pattern with two factors, factor I was the time of fermentation (20, 24, 28 hours) and factor II was the type of fruit (red guava, white guava, crystal guava). The data obtained were analyzed using ANOVA and if there was a significant difference between treatments, it was continued by further testing at 5% DMRT level. Crystal guava juice probiotic drink fermented for 28 hours was the best treatment, with the resulting physicochemical characteristics, namely pH 3.3; total BAL 9.09 log CFU/ml, total acid 0.89%, total sugar 5.38%, vitamin C content 152.24 mg. The resulting organoleptic properties include color, aroma, taste, overall 3.4 (slightly like), 3.65 (slightly like), 4.55 (like), 3.60 (slightly like).